COMPOSITION OF CELLULAR MEMBRANES IN THE PANCREAS OF THE GUINEA PIG : I. Isolation of Membrane Fractions - Meldolesi, J. (The Rockefeller University Press, 1971)
The subcellular components involved in the synthesis, transport, and discharge of secretory proteins in the guinea pig pancreatic exocrine cell have been isolated from gland homogenates by differential and gradient centrifugation. They include rough and smooth microsomes derived respectively from the rough endoplasmic reticulum and Golgi periphery, a zymogen granule fraction consisting mainly of mature zymogen granules and a smaller population of condensing vacuoles, and a plasmalemmal fraction. Membrane subfractions were obtained from the particulate components by treatment with mild (pH 7.8) alkaline buffers which extract the majority (>95%) of the content of secretory proteins, allowing the membranes to be recovered from the extracting fluid by centrifugation. The purity of the fractions was assessed by electron microscopy and by assaying marker enzymes for cross-contaminants. The rough and smooth microsomes were essentially free of mitochondrial contamination; the smooth microsomes contained <15% rough contaminants. The zymogen granule fraction and its derived membranes were free of rough microsomes and contained <3% contaminant mitochondria. The plasmalemmal fraction was heterogeneous as to origin (deriving from basal, lateral, and apical poles of the cell) and contained varying amounts of adherent fibrillar material arising from the basement membrane and terminal web. The lipid and enzymatic composition of the membrane fractions are described in the following reports.